The United Nations Multidimensional Integrated Stabilization Mission In Mali (MINUSMA) In Peacekeeping Support Operation In Mali (Journal of Namibian Studies : History Politics Culture, 2023)
This study seeks to assess the impact of the United Nations Multidimensional Integrated Stabilization Mission in Mali (MINUSMA) and identify challenges facing the United Nations Multidimensional Integrated Stabilization Mission in Mali (MINUSMA). The descriptive research design was adopted for this study and the data collected for this study collected from secondary sources such as textbooks, journals and other internet source while content analysis was used to analyse the data collected. This study is anchored on the institutional theory. This study revealed that the United Nations Multidimensional Integrated Stabilization Mission in Mali (MINUSMA) has made significant impact in the area of peace building for instance large numbers of displaced people were able to return home, the stability in northern Mali was improved, and the number of civilians killed in the fighting was reduced. Moreover, MINUSMA helped with the peace process that led to the 2015 Accord for Peace and Reconciliation in Mali, and aided the organising of the 2013 and 2016. However, MINUSMA is one of the costliest peacekeeping missions in Africa, with a budget of roughly $600 million and one of the deadliest peacekeeping support operations in the world in recent years considering the numbers of casualties recorded. Others include conflict over authority and labour allocation. In adequate personal and logistics issues are among the challenges facing MINUSMA. Lastly, this study recommended among other things that the present peace deal needs to be implemented honestly and successfully, since past peace accords' insufficient execution contributed to the revival of the problem in Mali.